Implementation of Online Learning for Islamic Cultural History Subjects - Sulaiman, Sulaiman; Fauzi, Saedul Ahmad; Indriyani, Fajar; Abulatifeh, Raed Fakhri (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: : This study aims to provide an overview of the process and results of implementing online learning of Islamic cultural history subjects at State Islamic High School 2 Cilacap. Methodology: The type of research used by the researcher in this study is field research using a qualitative descriptive approach. Main Findings: The results of this study include the objectives of online learning of Islamic cultural history subjects at State Islamic High School 2 Cilacap which consists of e-learning-based learning to make learning materials available to others. The benefits of online learning to overcome space and time limitations between teachers and students. The advantages and obstacles of online learning. Novelty/Originality of this study: The novelty of this study lies in its specific focus on Islamic Cultural History as part of religious education in Madrasah Aliyah, with an e-learning approach that utilizes a static station model to overcome the limitations of learning time.